1482 Occupational social class and self rated health. a cross sectional study of older irish adults from the irish longitudinal study on ageing. (24th April 2018) - Kelly, S; McCarren, A; Reid, A
Abstract : Introduction: Self-rated health has been shown to be an important predictor of future morbidity and mortality. We investigated the association between self-rated health and occupational social class in a population at work aged ≥50 years in Ireland, and determined its relationship with demographic and health-related variables. Methods: Cross-sectional data from The Irish Longitudinal Study on Ageing (TILDA), a population-based study of 8175 people aged ≥50 years was analysed. Those in employment were grouped according to the occupational social classification, an internationally recognised categorisation widely used to analyse social and health variations. Statistical analyses were performed using SPSS (V22.0, SPSS Inc, IL). Tests for main effects were conducted using an ordinal logistic regression using a generalised linear model. The relationship between self-rated health and social class was examined with age, gender, educational status, medical history and multiple lifestyle factors (body mass index (BMI), smoking, alcohol consumption, physical activity) as the independent variables. Results: 30% (2440/8175) of the TILDA cohort were in employment at the time of the study and therefore included in the analysis. There was a statistically significant association between self-rated health and occupational social class after adjusting for independent variables as described above (p-value 0.014). Conclusion: There is a strong cross-sectional association between self-rated health and occupational social class in those at work over 50 years of age in Ireland. This association is preserved after adjusting for gender, age, past medical history, lifestyle behaviours and educational status. Further research is required to establish if this association persists among retirees. This study confirms the need to tailor health promotion and well-being programs to the different occupational social groups to maximise potential health benefits and to preserve employment among older workers